Design and analysis of a 2.4 GHz hybrid type automatic amplitude control VCO with forward noise reduction - Zhang, Y. X (2014)
This paper presents a voltage-controlled oscillator (VCO) with automatic amplitude control (AAC) loop. The proposed AAC VCO employs a hybrid type AAC loop and targets the Industrial, Scientific and Medical (ISM) band applications. The proposed AAC loop can also prevent the AAC from generating extra noise to the VCO and avoid stability problem which is common for conventional AAC loop. Detail transient analysis of this AAC VCO is derived. Based on this analysis, design steps applicable for such type of AAC loop is obtained. Measurement result shows the peak amplitude variation over the operation range of 2.25-2.54 GHz is less than 9 mV (without the AAC loop, amplitude variation can be as large as 40 mV, or 22.2% for 180 mV amplitude). Power consumption of the proposed AAC VCO is 4.5 mW while the power consumed by the loop is 0.8 mW and phase noise is -105 dBc/Hz at 100 kHz offset frequency. Worst case settling time is less than 10.5 μs